The Effect of Applying the Maryam Delivery Method on the Comfort of Primigravida Mothers - Dila Nurhikmah; Feva Tridiyawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Labor is a process that is 90% dominated by pain that will arise at the first phase. The negative effects of labor pain include maternal metabolic acidemia, fetal acidosis, and dysfunctional labor. Pharmacological methods using chemical drugs, tend to be more expensive and potentially have side effects. childbirth modification methods with various techniques, one of which is Maryam's labor technique. The purpose of this study was to analyze the effect of deep breath relaxation techniques on comfort characterized by a decrease in pain intensity. This study used an experimental quasy design. The location used forÂ¬Â¬this research is at PMB Yeni Nurhayani, S.Tr., Pandeglang District from April to May 2023. The population used in this study was maternity mothers at the study site during the study process as many as 30 mothers selected by purposive sampling. Maryam's technique is done by positioning the body standing leaning on something sturdy with a half-squat position and legs wide open. The instrument used in this study was the Verbal Analog Scale. The analysis used is multiple linear regression. The mean degree of pain decreased after Maryam's technical intervention (Mean= 5.80; SD=1.34) was lower than before Maryam's therapy (Mean= 4.90; SD= 1.15), and statistically significant (p<0.001).